Association of quantitative CT lung density measurements and lung function decline in World Trade Center workers. (29th December 2020) - Liu, Xiaoyu; Reeves, Anthony P.; Antoniak, Katherine; San José Estépar, Raúl; Doucette, John T.; Jeon, Yunho; Weber, Jonathan; Xu, Dongming; Celedón, Juan C.; de la Hoz, Rafael E.
Abstract: Background: Occupational exposures at the WTC site after 11 September 2001 have been associated with presumably inflammatory chronic lower airway diseases. Aims: In this study, we describe the trajectories of expiratory air flow decline, identify subgroups with adverse progression, and investigate the association of those trajectories with quantitative computed tomography (QCT) imaging measurement of increased and decreased lung density. Methods: We examined the trajectories of expiratory air flow decline in a group of 1, 321 former WTC workers and volunteers with at least three periodic spirometries, and using QCT‐measured low (LAV%, −950 HU) and high (HAV%, from −600 to −250 HU) attenuation volume percent. We calculated the individual regression line slopes for first‐second forced expiratory volume (FEV1 slope), identified subjects with rapidly declining ("accelerated decliners") and increasing ("improved"), and compared them to subjects with "intermediate" (0 to −66.5 mL/year) FEV1 slope. We then used multinomial logistic regression to model those three trajectories, and the two lung attenuation metrics. Results: The mean longitudinal FEV1 slopes for the entire study population, and its intermediate, decliner, and improved subgroups were, respectively, −40.4, −34.3, −106.5, and 37.6 mL/year. In unadjusted and adjusted analyses, LAV% and HAV% were both associated with "accelerated decliner" status (ORadj, 95% CI 2.37, 1.41–3.97, and 1.77, 1.08–2.89, respectively), compared to the intermediate decline. Conclusions: Longitudinal FEV1 decline in this cohort, known to be associated with QCT proximal airway inflammation metric, is also associated with QCT indicators of increased and decreased lung density. The improved FEV1 trajectory did not seem to be associated with lung density metrics.